Equation 1) y - 2x = 3
Equation 2) 3x - 2y = 5
Switch around x and y in equation 1.
1) -2x + y = 3
2) 3x - 2y = 5
Multiply ALL of equation 1 by 2.
1) 2(-2x + y = 3)
Simplify.
1) -4x + 2y = 6
2) 3x - 2y = 5
Add equations together.
-x = 11
Divide both sides by -1.
x = -11
Plug in -11 for x in the first equation.
-4x + 2y = 6
-4(-11) + 2y = 6
Simplify.
44 + 2y = 6
Subtract 44 from both sides.
2y = 6 - 44
Simplify.
2y = -38
Divide both sides by 2.
y = -38/2
y = -19
So, x = -11, y = -19
D : (-11, -19)
~Hope I helped!~